Translating Indigeneity at the University of Alberta - Malena, Anne; Tarif, Julie (TTR : traduction, terminologie, rédaction, 2018)
Over the last few years there has been an attempt to redress the asymmetrical relations between Canada’s First Nations, Métis, and Inuit people, and the non-Indigenous people in Canada. Post-secondary education plays a prominent role in this endeavour and many institutions across Canada are currently working on innovative ways to make their environment more inclusive, or what is called “Indigenizing” the academy. This study focuses on how the University of Alberta (Edmonton) is meeting this challenge and argues that a form of activist translation needs to be an important part of this endeavour in order to redress damages caused by colonialism. Des efforts sont faits depuis quelques années pour améliorer les relations asymétriques qui existent au Canada entre les Premières Nations, les Métis, les Inuit et le peuple non autochtone. Les institutions post-secondaires jouent un rôle clé dans cette entreprise d’« Indigénisation », et plusieurs d’entre elles s’attachent, par le biais de projets novateurs, à rendre l’environnement universitaire plus inclusif pour les étudiants autochtones. Cette étude s’intéresse aux stratégies utilisées par l’Université de l’Alberta (Edmonton) pour faire face à ce défi et postule qu’il est important de mettre en place une forme de traduction activiste au sein de cette entreprise afin de redresser les torts du colonialisme.